Breaking the zero-sum game : transforming societies through inclusive leadership - Boitanode Moras, Aldo; Lagomarsino Dutra, Raúl; Schockman, H. Eric (Building leadership bridges., 2017)
In a world plagued by wicked problems, escaping the win-lose dynamics of zero-sum game approaches is crucial for finding integrated, inclusive solutions to complex issues. In this book, the reader will uncover real-life examples of inclusive leaders that have broken the zero-sum game. From Ivy League colleges to African villages, from the very top of the Catholic Church to anarchist conferences and meetings, inclusive leadership can be applied - and the protagonists will tell you how. As the examples in the book demonstrate, inclusive leadership is not the privilege of a few gifted individuals with extraordinary human qualities. Inclusive leaders are not necessarily charismatic (like Nelson Mandela, Gandhi, or Martin Luther King, Jr). The vast majority of inclusive leaders are just regular everyday people. They only differ - and what a difference it makes! - in being able to turn what seem to be zero-sum problems into opportunities for inclusiveness. Including a foreword from Edwin Hollander, a pioneering visionary of inclusive leadership, you will find concrete examples and tools in this book that you can start using from day one (and in your own way) as an inclusive leader.